2003
DOI: 10.1152/japplphysiol.01054.2002
|View full text |Cite
|
Sign up to set email alerts
|

B-1 cell (CD5+/CD11b+) numbers and nIgM levels are elevated in physically active vs. sedentary rats

Abstract: Habitual, moderate exercise is associated with improved health, including reductions in illness. These benefits may stem, in part, from immune function improvements. We have previously reported that daily wheel running increases serum and peritoneal natural IgM (nIgM) in pathogen-free Sprague-Dawely rats. B-1 cells, which primarily reside in the peritoneal cavity, produce nIgM in the absence of antigen stimulation. This study examined whether physical activity would also increase B-1 cell numbers in the perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…'B1' cells are a population of B cells, originally identified in mice that produce high levels of low-affinity natural antibody. In rats, it has been shown that natural IgM and B1 cells are increased in physically active versus sedentary animals, but the effects of exercise in humans has remained unclear [11,12]. Recently, however, it has been shown that the phenotypic markers proposed for purported human 'B1' cells are, in fact, a population of pre-plasmablasts in humans [6].…”
Section: Discussionmentioning
confidence: 99%
“…'B1' cells are a population of B cells, originally identified in mice that produce high levels of low-affinity natural antibody. In rats, it has been shown that natural IgM and B1 cells are increased in physically active versus sedentary animals, but the effects of exercise in humans has remained unclear [11,12]. Recently, however, it has been shown that the phenotypic markers proposed for purported human 'B1' cells are, in fact, a population of pre-plasmablasts in humans [6].…”
Section: Discussionmentioning
confidence: 99%
“…The B-1 cell is a subset of murine B cells and expresses CD11b. [16][17][18] They primarily reside in the peritoneal cavity and, by producing IgM, are known to play an important role in host defense. However, the B-cell system of human beings is known to be distinct from that of mouse or rat.…”
Section: Discussionmentioning
confidence: 99%
“…Kyaw et al 43 44 showed the action of B1 cells in atheroprotective activity by the production of nIgM. Elphick et al 45 46 demonstrated, in an animal model, that training increases the production of nIgM. We observed that immediately after and up to 72 h after a marathon race, the levels of the IgM isotype anti-oxLDL autoantibodies remain unchanged, in contrast to the effect that would be expected if the autoantibody were acting to block the oxLDL.…”
Section: Discussionmentioning
confidence: 54%